The Patterns of Participatory Communication in Empowering the MSMEs Sector - Yuliasari, Ika; Elizabeth Ayuna, Novianty; Ayu Permatasari, Mega (Asian Journal of Social and Humanities, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in enhancing community economies, especially in the digital era. This article examines MSME actors in batik handicrafts in the Giriloyo area of Yogyakarta and weaving craftsmen in the Baduy area of Banten. The Indonesian government's development programs aim to empower MSMEs in tourist villages, fostering independence and community participation while preserving cultural heritage. Despite being in rural areas, these artisans have successfully promoted their products globally through communication technology. The research highlights the socio-cultural backgrounds of these communities, enriching findings on communication patterns and MSME sector empowerment. Employing a qualitative approach, data was gathered through observation, interviews, documentation, and focus group discussions. The analysis reveals that MSME actors primarily develop participatory communication networks to enhance marketing strategies for batik and woven products. Key findings include increased community engagement, expanded partnerships, fostered dialogical interactions, direct sales growth, and enhanced social media promotion. The research contributes to the theory of participatory communication in the digital era, marketing communication models, and MSME empowerment strategies. Practical implications suggest effective communication network development and business communication enhancement for MSMEs.